The perceptions of teachers and heads of department on the roles of a formal mentor in a Zambian Secondary School (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
This paper reports on research work concerning the perceptions of newly qualified teachers (NQTs) and heads of department (HoDs) regarding the roles of formal mentors in helping newly qualified teachers in selected secondary schools in Zambia. These NQTs could be products of a conventional teacher preparation programme through fulltime study, part-time or parallel study, or an Open and Distance Learning Programme. The purpose of the study was to establish what NQTs and HoDs believed to be key areas in which NQTs needed to be mentored in order to help them adapt to the requirements of their teaching roles in schools. It uses quantitative data that were collected from the NQTs and HoDs using self-administered questionnaires guided by Kram’s Mentor Role Theory. Data were collected from a sample of 191 participants that comprised 92 NQTs and 99 HoDs. Quantitative data were analysed using the Chi Square test. Quantitative results suggest that there was a huge discrepancy in the perceptions of NQTs and HoDs regarding the roles of a formal mentor in helping NQTs in their work. The paper proposes the development of a policy on mentorship of NQTs and a mentorship framework to ensure harmonization of understanding of mentorship and its effective implementation.
Keywords: Perceptions; newly qualified teachers; formal mentor; mentoring; school-based support; initial teacher education